The role of chaperones in Parkinson's disease - Winklhofer, Konstanze F. (Henry Stewart Talks, 2007)
Parkinson's disease, Pathophysiology, neuropathology, etiology, Genes associated with Parkinson's disease, Role of protein misfolding in Parkinson's disease, alpha-synuclein: protein misfolding and a gain of toxic function, Parkin: protein misfolding and a loss of physiological function, Effect of chaperones in different models of Parkinson's disease
Archived at 2021/02/25